Comparing the Compassion-Based GASING Method and CPA Approach on Addition Learning Outcomes of Fourth-Grade Elementary Students - Jeni Kada Saripi; Tita Mulyati; Rendi Restiana Sukardi (Universitas Lambung Mangkurat, 2026)
Low mathematics learning outcomes among elementary school students remain a persistent challenge in Indonesia, particularly in regions characterized by diverse socio-cultural backgrounds and limited instructional resources. This study investigated the comparative effectiveness of the compassion-integrated GASING method and the Concrete Pictorial Abstract (CPA) approach in enhancing mathematics achievement among fourth-grade elementary students in Nabire Regency, Papua. A quasi-experimental nonequivalent control group design was employed, with 125 students from six elementary schools comprising the analyzed sample, of whom 59 were assigned to the experimental group receiving the compassion-integrated GASING method and 66 to the control group receiving the CPA approach. Data were collected through a 20-item multiple-choice mathematics achievement test covering addition operations, validated through Pearson correlation analysis and demonstrating high reliability (Cronbach's Alpha = 0.871). The enactment of the compassion-integrated GASING method was assessed through structured observation checklists completed by classroom teachers at each session, yielding a mean implementation fidelity of 99.19%, compared to 97.22% for the CPA approach, with both classified as Very Good. Inferential analysis proceeded in two stages. The Wilcoxon Signed-Rank test revealed statistically significant within-group gains in both the experimental group (Z = -6.689, p < .001, r = 0.871) and the control group (Z = -7.017, p < .001, r = 0.864), with both effect sizes classified as large. The Mann-Whitney U test subsequently indicated no statistically significant between-group difference in posttest outcomes (U = 1826.000, Z = -0.601, p = .548, r = 0.054). These findings confirm that both approaches produced comparably equivalent and practically significant gains in mathematics learning outcomes. The high fidelity of compassion-based instruction observed across all sessions provides empirical support for the consistent enactment of the affective dimension of the intervention, though its direct impact on students' emotional outcomes warrants further investigation using validated affective instruments. These findings suggest that teachers in diverse and underserved elementary settings may confidently adopt either approach, with the compassion-integrated GASING method offering additional promise as a contextually responsive instructional model.